Diversidad social en perspectiva de Trabajo Social intercultural (2014)
ABSTRACT: Social diversity refers to all human manifestations of variety and rupture against the singlesubject and the undimensional modern society. Its wide recognition in Latin America by governments of the region, from the second half of the twentieth century to today, has transformed it into unquestionable social evidence and a category of scholarly analysis. We are therefore, helping its naturalization and institutionalization as an expression of uniqueness and rupture from society within a Western perspective. On this historical moment, the question to ask is: Where will so much recognition lead? This article aims at reflecting on the complexity associated with the social and political recognition of social diversity, warning us about <loose ends> or issues to be resolved in relation to our human subjectivity given that objectively it appears its recognition is resolved, and presenting a critical analysis of interculturality as a horizon for Latin American social work.